2000
DOI: 10.1074/jbc.275.15.11418
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of p38 Mitogen-activated Protein Kinase Is an Early Regulatory Event for the Cadmium-induced Apoptosis in Human Promonocytic Cells

Abstract: Pulse treatment of U-937 promonocytic cells with cadmium chloride (2 h at 200 M) provoked apoptosis and induced a rapid phosphorylation of p38 mitogen-activated protein kinase (p38 MAPK ) as well as a late phosphorylation of extracellular signal-regulated protein kinases (ERK1/2). However, although the p38 MAPK -specific inhibitor SB203580 attenuated apoptosis, the process was not affected by the ERK-specific inhibitor PD98059. The attenuation of the cadmium-provoked apoptosis by SB203580 was a highly specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
94
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(105 citation statements)
references
References 49 publications
(28 reference statements)
8
94
3
Order By: Relevance
“…Many reports suggested that JNK or p38 MAPK induces apoptosis by regulating the translocation of Bax from the cytoplasm to the mitochondria in response to various stimuli (12)(13)(14). These results are consistent with the fact that JNK and/ or p38 MAPK acts at early step before dysfunction of mitochondria and caspase activation in several cell types (15)(16)(17). In contrast, recent observations showed that p38 MAPK is a critical regulator of cell survival and proliferation in response to cisplatin, camptothecin, doxorubicin, UV irradiation, and repetitive low-grade oxidative stress (18)(19)(20).…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Many reports suggested that JNK or p38 MAPK induces apoptosis by regulating the translocation of Bax from the cytoplasm to the mitochondria in response to various stimuli (12)(13)(14). These results are consistent with the fact that JNK and/ or p38 MAPK acts at early step before dysfunction of mitochondria and caspase activation in several cell types (15)(16)(17). In contrast, recent observations showed that p38 MAPK is a critical regulator of cell survival and proliferation in response to cisplatin, camptothecin, doxorubicin, UV irradiation, and repetitive low-grade oxidative stress (18)(19)(20).…”
Section: Introductionsupporting
confidence: 79%
“…Many reports suggested that p38 MAPK induces apoptotic cell death in response to various stimuli (15)(16)(17). In contrast, in this study we showed that p38 MAPK played a role in cell survival response against radiation-induced mitochondrial cell death.…”
Section: Discussioncontrasting
confidence: 52%
“…Furthermore, ERK expression in NIH 3T3 cells impairs the majority of the UV-induced apoptotic response (14). The prosurvival function of ERK was confirmed in a recent report showing that inhibition of ERK signaling leads to increased sensitivity to cisplatin (cis-diammine-dichloroplatinum) in ovarian cancer cells (31). Conversely, activation of the MEK/ ERK signaling pathway in activated Jurkat T cells suppresses tumor necrosis factor-related apoptosis-inducing ligand -mediated apoptosis in a similar manner to Fas-mediated apoptosis (30).…”
Section: Discussionmentioning
confidence: 58%
“…However, p38 was not associated with activation of caspase-8 in exerting such roles , suggesting that at least two parallel signaling pathways exist above Bid. Recently, it has been shown that p38 activation is also required for the release of cytochrome c from mitochondria in the apoptosis induced by cadmium and UV light, supporting the idea that p38 functions upstream of mitochondria in mediating activation of caspase-3 (Assefa et al, 2000;Galan et al, 2000). In the case of singlet oxygen, caspase-3 activation is su cient for induction of apoptosis (Zhuang et al, 1999); thus, inactivation of caspase-8 and/or p38 pathways may allow cells to escape apoptosis following singlet oxygen treatment.…”
Section: Introductionmentioning
confidence: 69%